Um estudo das condições de percolação e estabilidade em barragens de terra mediante métodos geofísicos: caso do dique de Sant Llorenç de Montgai - Espanha - Teixeira, Washington Luiz Evangelista (2013)
The monitoring of Earth dam makes use of visual inspection and instrumentation to identify and characterize the deterioration that compromises the security of earth dams and associated structures. The visual inspection is subjective and can lead to misinterpretation or omission of important information and, some problems are detected too late. The instrumentation are efficient but certain technical or operational issues can cause restrictions. Thereby, visual inspections and instrumentation can lead to a lack of information. Geophysics offers consolidated, low-cost methods that are non-invasive, non-destructive and low cost. They have a strong potential and can be used assisting instrumentation. In the case that a visual inspection and strumentation does not provide all the necessary information, geophysical methods would provide more complete and relevant information. In order to test these theories, geophysical acquisitions were performed using Georadar (GPR), Electric resistivity, Seismic refraction, and Refraction Microtremor (ReMi) on the dike of the dam in Sant Llorenç de Montgai, located in the province of Lleida, 145 km from Barcelona, Catalonia. The results confirmed that the geophysical methods used each responded satisfactorily to the conditions of the earth dike, the anomalies present and the geological features found, such as alluvium and carbonate and evaporite rocks. It has also been confirmed that these methods, when used in an integrated manner, are able to reduce the ambiguities in individual interpretations. They facilitate improved imaging of the interior dikes and of major geological features, thus inspecting the massif and its foundation. Consequently, the results obtained in this study demonstrated that these geophysical methods are sufficiently effective for inspecting earth dams and they are an important tool in the instrumentation and visual inspection of the security of the dams